2019
DOI: 10.7717/peerj.7988
|View full text |Cite
|
Sign up to set email alerts
|

Endless forms of sexual selection

Abstract: In recent years, the field of sexual selection has exploded, with advances in theoretical and empirical research complementing each other in exciting ways. This perspective piece is the product of a “stock-taking” workshop on sexual selection and sexual conflict. Our aim is to identify and deliberate on outstanding questions and to stimulate discussion rather than provide a comprehensive overview of the entire field. These questions are organized into four thematic sections we deem essential to the field. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 327 publications
(421 reference statements)
1
16
0
1
Order By: Relevance
“…Kemp [ 78 ] found that in Eurema hecabe , male UV brightness correlates with their body size and, interestingly, also with the size of their mate. This supports the hypothesis for the complexity of sexual interactions in polyandrous pierid butterflies, including, for instance, potential assortative mating [ 8 , 85 ]. Furthermore, one study found multiple quality-revealing sexual ornaments (nest features, plumage quality, ecoparasite load, body size) in bowerbirds, suggesting that bowers are an extension of the male phenotype that females can use to assess male quality [ 86 ].…”
Section: The Adaptive Function Of Uv Reflectance and Its Perception I...supporting
confidence: 85%
See 1 more Smart Citation
“…Kemp [ 78 ] found that in Eurema hecabe , male UV brightness correlates with their body size and, interestingly, also with the size of their mate. This supports the hypothesis for the complexity of sexual interactions in polyandrous pierid butterflies, including, for instance, potential assortative mating [ 8 , 85 ]. Furthermore, one study found multiple quality-revealing sexual ornaments (nest features, plumage quality, ecoparasite load, body size) in bowerbirds, suggesting that bowers are an extension of the male phenotype that females can use to assess male quality [ 86 ].…”
Section: The Adaptive Function Of Uv Reflectance and Its Perception I...supporting
confidence: 85%
“…Female preference for males with brighter UV patterns was also found in Hypolimnas bolina [ 76 ]. A key prediction of the honest signalling theory is that the expression of directionally selected sexual traits should tightly co-vary with the condition of the phenotype [ 25 , 85 ]. This phenomenon is known as ‘condition-dependence’ [ 102 ].…”
Section: The Adaptive Function Of Uv Reflectance and Its Perception I...mentioning
confidence: 99%
“…In addition to credibility, multiple selection pressures can shape signals, including biases in the sensory systems of receivers; receiver abilities to discriminate signals; the structure of the environment; social challenges; and arms races between signalers and receivers (Krebs & Dawkins 1984), where signalers are selected to produce the signal at lower cost and receivers are selected to better discriminate the quality of signalers (Bradbury & Vehrencamp 1998;Cummings & Endler 2018;Doorn & Weissing 2006;Hill 1994;Lindsay et al 2019;McCoy & Haig 2020).…”
Section: Origins Of Music In Credible Signalingmentioning
confidence: 99%
“…Differences between the sexes also play a major role in determining among-population variation in socio-sexual and locomotor behaviors. Classically defined sex roles suggest that sexual selection should be stronger on males than females, as lower costs of gamete investment for males lead to greater benefits of multiple mating (Bateman, 1948;Lindsay et al, 2019). Consequently, males are generally expected to invest more of their time and energy engaged in courtship behaviors to attract partners (inter-sexual selection) and agonistic behaviors toward rivals to compete for reproductive opportunities (intra-sexual selection; Andersson, 1994).…”
Section: Introductionmentioning
confidence: 99%